The double-edged sword of leader humility: Investigating when and why leader humility promotes versus inhibits subordinate deviance - Qin, Xin; Chen, Chen; Yam, Kai Chi; Huang, Mingpeng; Ju, Dong (Journal of applied psychology, 2020)
Extant research has uniformly demonstrated that leader humility is beneficial for subordinates, teams, and even organizations. Drawing upon attribution theory, we challenge this prevailing conclusion by identifying a potential dark side of leader humility and suggesting that leader humility can be a mixed blessing. We propose that the effects of leader humility hinge on subordinates' attributions of such humble behavior. On the one hand, when subordinates attribute leader humility in a self-serving way, leader humility is positively associated with subordinate psychological entitlement, which in turn increases workplace deviance. On the other hand, when subordinates do not attribute leader humility in a self-serving way, leader humility is positively associated with leader-member exchange, which in turn decreases workplace deviance. We found support for our hypotheses across a field study and an experiment. Taken together, our findings reveal the perils and benefits of leader humility and the importance of examining subordinate attributions in this unique leadership process. (PsycInfo Database Record (c) 2020 APA, all rights reserved).